Constructing coral-like hierarchical porous carbon architectures with tailored pore size distribution as sulfur hosts for durable Li-S batteries. (1st May 2021) - Hu, Qianqian; Dong, Haiyong; Wang, Biao; Yang, Chun; Wang, Xuyao; Lu, Jiqun; Hong, Ye; Zhang, Lingzhi
Abstract: Structural hierarchy of porous carbon has been a key role in the sulfur hosts for lithium sulfur (Li-S) batteries. Herein, coral-like hierarchical porous carbon (HPC) is developed by a dual alkaline activation process. The production of HPC is inexpensive and scalable, which gives a great promise as sulfur host for the future application of Li-S batteries. Moreover, the as-prepared material achieves an admirable interconnected conductive network, hierarchical pore size distribution and notably high pore volume. This architecture contributes to ultrafast ion diffusion, rapid mass transport, robust electrode configuration as well as effective physical adsorption for soluble polysulfide, thus enabling a favorable scaffold for Li-S battery cathodes with high sulfur utilization and exceptionally electrochemical stability. As a consequence, the HPC based sulfur cathode manifests high areal capacity of 7.5mAh/cm 2 with a high sulfur loading and superb cycling stability over 500 cycles with lower sulfur loading. The classification of alkali significantly affects on the hierarchical porosity of the resultant carbon. And the correlation between the pore size distribution and electrochemical performance is revealed. This work offers a hierarchical material engineering of a sulfur host material for restricting the mobile polysulfide moieties, thus achieving a high efficiency and stable Li-S battery. Table of contents: Coral-like hierarchical porous carbon (HPC) is developed by a dual alkaline activation process. The obtained material manifests high surface area, pore volume and hierarchical pores. When used as a sulfur host, such material is advantageous for ultrafast ion diffusion, rapid mass transport, robust electrode configuration as well as an effective physical adsorption for soluble polysulfides. Attributed to the above merits, HPC based sulfur electrode shows a high specific capacity with a high sulfur loading up to 6 mg/cm 2 and superb cycling stability over 500 cycles with lower sulfur loading. Image, graphical abstract